2002
DOI: 10.1164/rccm.2110066
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Balance between Myeloid Dendritic Cells and Plasmacytoid Dendritic Cells in Peripheral Blood of Patients with Asthma

Abstract: Asthma, a well-known helper T cell Type 2 (Th2)-mediated disease, has a polarized immune response toward a Th2 phenotype. However, the factors causing the Th2 polarization remain to be fully determined in this disease. Dendritic cells (DCs) are the most potent antigen-presenting cells that play a central role in initiating the primary immune response. In human blood, two functional distinct subsets of DCs, myeloid DCs and plasmacytoid DCs, have been identified. Myeloid DCs (mDCs) and plasmacytoid DCs (pDCs) ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 35 publications
2
62
1
Order By: Relevance
“…In support of this hypothesis, we have previously reported that pDCs play an essential role in maintaining tolerance in the lung when naive mice were exposed to harmless inhaled Ags (16). The critical involvement of various DC subsets in promoting or dampening inflammation has been reported in several other models, in which also viral Ags were used (35)(36)(37)(38)(39)(40). However, these experiments were done in the context of a primary immune response, as pDCs were given or depleted at the time of sensitization.…”
Section: Discussionmentioning
confidence: 81%
“…In support of this hypothesis, we have previously reported that pDCs play an essential role in maintaining tolerance in the lung when naive mice were exposed to harmless inhaled Ags (16). The critical involvement of various DC subsets in promoting or dampening inflammation has been reported in several other models, in which also viral Ags were used (35)(36)(37)(38)(39)(40). However, these experiments were done in the context of a primary immune response, as pDCs were given or depleted at the time of sensitization.…”
Section: Discussionmentioning
confidence: 81%
“…Indeed, pDCs have been shown capable of mediating both Th1 and Th2 polarization (15,34). Furthermore, studies in humans show that both mDCs as well as pDCs are present in the allergic immune response to allergen (35,36) and, in patients with allergic asthma, allergen challenge increased both mDC and pDC numbers with an overall greater percent increase in pDCs (37). Clearly, the precise role of different dendritic cells subsets in allergic diseases is far from resolved.…”
Section: Discussionmentioning
confidence: 99%
“…In two preliminary experiments, no increase in CD207 (the Langerhans marker) was detected on low MLR-capacity patient M , but these data are far from conclusive. A posttrauma increase in plasmacytoid or lymphoid-derived DC precursors could greatly affect overall DC APC capacity (15,16,49). The plasmacytoid DC population is suggested to preferably induce regulatory T cells (15,16).…”
Section: Discussionmentioning
confidence: 99%